Cracking-resistant high-performance halogen-free flame-retardant PC alloy material and preparation method thereof

By using SEBS grafted maleic anhydride, POE grafted maleic anhydride and halogen-free flame retardant in flame retardant PC alloy materials, combined with talc powder and resistant modifiers, the flame retardant PC alloy materials are solved. The problem of prone to cracking after injection molding has achieved a balance of weather resistance and flame retardancy of the material, which significantly improves the ductility and creep resistance of the material.

CN119144137APending Publication Date: 2024-12-17SHANGHAI KUMHOSUNNY JINSHAN PLASTICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411285674.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Flame-retardant PC alloy materials are prone to internal stress during injection molding, which leads to prone to cracking after assembly, and the prior art is difficult to balance when improving the weather resistance and rigidity of the material, resulting in assembly failure.

Method used

Using SEBS grafted maleic anhydride and POE grafted maleic anhydride as cracking modifiers, combining halogen-free flame retardants such as bisphenol A-bis(diphenylphosphate) and methyl acrylate-butadiene-styrene talc powder and crystalline resin are added, and maleic anhydride and resistant modifier are grafted with specific thermoplastic olefin-based elastomers to reduce the amount of butadiene powder, improve the ductility of the material and Cracking resistance.

Benefits of technology

It effectively improves the low-temperature toughness and creep resistance of the material, avoids cracking problems caused by long-term placement after assembly and weather changes, maintains flame retardant stability and gives a comfortable surface touch.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005043053200000021
    Figure BDA0005043053200000021
  • Figure BDA0005043053200000031
    Figure BDA0005043053200000031
  • Figure BDA0005043053200000061
    Figure BDA0005043053200000061
Patent Text Reader

Abstract

The invention discloses a cracking-resistant high-performance halogen-free flame-retardant PC alloy material and a preparation method thereof. The material is prepared from 50 to 85 parts of PC resin, 8 to 15 parts of halogen-free flame retardant, 5 to 15 parts of flexibilizer, 1 to 5 parts of cracking modifier, 3 to 10 parts of chemical resistance modifier, 0.3 to 0.5 part of talcum powder, 0.2 to 0.5 part of lubricant and 0.2 to 0.5 part of antioxidant. The material is endowed with excellent low-temperature toughness and creep resistance, and the problems that parts formed by injection molding of the flame-retardant PC alloy crack after being assembled and parts crack after being placed for a long time and the weather turns cold are effectively solved. Wherein the talcum powder effectively neutralizes acidic substances generated due to decomposition of a flame retardant in the screw extrusion process, and degradation of a PC base material is reduced; the slow crystallization rate of the chemical-resistant modifier PET can inhibit the movement of a PC molecular chain, so that the PC stress is slowly released, and the equilibrium state is better achieved; the cracking modifier endows the material with higher ductility and toughness, promotes the compatibility of the material, and can endow the surface of a workpiece with comfortable touch feeling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of PC alloy materials, and relates to a crack-resistant, high-performance, halogen-free, flame-retardant PC alloy material and a preparation method thereof. Background Art

[0002] Flame-retardant PC / ABS, PC / polyester and other PC alloy materials are widely used in various industries due to their excellent flame retardancy and outstanding rigidity-toughness balance. The application scenarios include but are not limited to the electrical industry, security industry, OA industry, 3C electronics, new energy battery industry, etc. The application components are also different, and most of them are used in the outer casing of electronic and electrical products. Such components usually have strict flame retardant requirements to prevent internal circuit short circuits from causing material ignition and fire. At the same time, such shell parts usually have a variety of self-tapping screw columns and nut insert structures for assembly to adapt to various assembly scenarios. Since the flame-retardant PC alloy has a benzene ring with large steric hindrance on the molecular chain of PC, it is very easy to generate internal stress in the part during the injection molding process. The screw column is prone to cracking after assembly, resulting in assembly failure. The cracking forms vary. Some materials crack when the screws are driven in. In addition, there are various situations such as easy cracking in winter but not in summer, not cracking during assembly but cracking after being placed for a period of time, not cracking in one place but cracking in another place. Each failure situation has different attributions, such as unreasonable screw column size structure, poor material performance, chemical erosion, etc., multiple causes and different results. Therefore, in addition to external conditions such as assembly, the comprehensive balance of ductility, strength and toughness of the flame-retardant PC alloy material itself and low-temperature mechanical properties is very important to strictly avoid cracking in weak parts of parts, resulting in assembly or application failure.

[0003] A search of existing patent documents revealed that CN 107163533 A describes a PC / ABS alloy that prevents screw hole cracking. The anti-stress cracking agent EMA is added to improve the fluidity and toughness of the material and reduce the internal stress of the material during the injection molding process. The compatibilizer EMA-g-GMA is added to improve the compatibility of EMA and PC / ABS. However, the addition amount of EMA and EMA-g-GMA should not exceed 2%, otherwise EMA will cause the material to delaminate and peel. EMA-g-GMA contains reactive epoxy functional groups, which will reduce the fluidity of the material and increase the internal stress of the material. Therefore, a balance point is required. In addition, the addition of EMA will cause a serious decrease in the strength of the material, and the overall structure of the assembly will be soft, which is not a good choice for certain situations with high strength requirements.

[0004] CN 112812533 ​​A describes a halogen-free flame-retardant PC alloy material with high elongation at break, high performance retention rate under high temperature and high humidity, and strong resistance to chemical reagents. The material can effectively solve the problem of easy breakage of screw columns and buckles on the housing of electronic appliances, but it is mainly toughened by adding ABS and MBS, which has a great influence on the weather resistance and rigidity of the material. Summary of the invention

[0005] The object of the present invention is to provide a crack-resistant high-performance halogen-free flame-retardant PC alloy material and a preparation method thereof.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] The present invention provides a crack-resistant high-performance halogen-free flame-retardant PC alloy material, comprising the following components in parts by weight:

[0008]

[0009] The crack modifier is one or more of SEBS grafted maleic anhydride and POE grafted maleic anhydride.

[0010] The PC resin is preferably one or more PC compounded resins having a weight average molecular weight of 21,000-33,000.

[0011] The halogen-free flame retardant is preferably one or more of bisphenol A-bis(diphenyl phosphate) (BDP), triphenyl phosphate (TPP), resorcinol bis(diphenyl phosphate) (RDP), solid phosphate, and phosphazene.

[0012] The toughening agent is preferably one or more of methyl acrylate-butadiene-styrene (MBS), styrene-butadiene-acrylonitrile (ABS), and ethylene-methyl acrylate (EMA). EMA itself is a long-chain modifier, and its addition can easily lead to a significant decrease in the rigidity of the material. The presence of vinyl can cause the material to be prone to stratification and other poor compatibility problems; and when using ABS and MBS for toughening, in order to achieve the high crack resistance of the material, the addition amount must be ≥15%. Due to the presence of butadiene, the weather resistance of the material will deteriorate, and the addition of a large amount of rubber powder will also lead to a decrease in the rigidity of the material. The present invention uses a specific thermoplastic olefin elastomer grafted with maleic anhydride, and a small amount of addition can greatly reduce the addition amount of butadiene rubber powder, and will not have a huge impact on rigidity like EMA-type long-chain toughening agents, and can well improve the ductility and crack resistance of the material, giving it a comfortable surface touch.

[0013] The chemical resistance modifier is preferably a crystalline resin, more preferably polyethylene terephthalate (PET) having a viscosity of 0.65-0.85.

[0014] The talc powder is preferably talc powder with a particle size of 3000-5000 mesh and a surface that has not been treated with a coupling agent. In the system of the present invention, the role of talc powder is mainly to synergistically flame retardant and neutralize the acidic substances produced by the decomposition of the flame retardant. Pure phosphate flame retardant may fail to flame retard after thermal aging, and adding a small amount of talc powder can effectively improve it; in addition, during the processing, some phosphate flame retardants may decompose to produce phosphoric acid, which will cause a certain degree of degradation of PC, resulting in impact drop or appearance problems such as silver wire at the part gate; the present invention aims to develop a crack-resistant flame-retardant PC / ABS alloy, which needs to improve the material's crack resistance while maintaining the existing performance.

[0015] The lubricant is preferably one or more of ethylene bisstearamide, polyethylene wax, polypropylene wax, ethylene-vinyl acetate copolymer, and pentaerythritol tetrastearate.

[0016] The antioxidant is preferably one or both of antioxidant 1076 and antioxidant 168.

[0017] The anti-drip agent is preferably a PTFE anti-drip agent, including a coated PTFE anti-drip agent.

[0018] The present invention also provides a method for preparing a crack-resistant high-performance halogen-free flame-retardant PC alloy material, the method comprising the following steps:

[0019] (1) Prepare the following components by weight:

[0020]

[0021] (2) The toughening agent, crack modifier and chemical resistance modifier (weighed separately) in step (1) are first blended, then mixed with the remaining components according to the above weight proportions (added to a high-speed mixer and fully mixed), and then fed into a twin-screw extruder for blending and granulation; if the flame retardant is a liquid, it is fed separately from a liquid pump in a corresponding proportion.

[0022] In the above step (2), the extrusion process is to perform melt extrusion at an extrusion temperature of 240-270° C. and a screw speed of 200-500 rpm, and then cool and granulate to obtain the crack-resistant high-performance halogen-free flame-retardant PC alloy material.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The technical solution adopted by the present invention can give the material excellent low-temperature toughness and creep resistance, and can effectively solve the problem of cracking of parts made of flame-retardant PC alloy materials injection-molded after long-term storage after assembly and cracking of parts when the weather turns cold.

[0025] (2) The talc powder in the present invention can effectively neutralize the acidic substances produced by the decomposition of the flame retardant during the screw extrusion process, reducing the degradation of the PC substrate, which is the key to giving the material better creep resistance and maintaining flame retardant stability.

[0026] (3) The chemical-resistant modifier of the present invention is different from the PBT commonly used on the market. PET with a slower crystallization rate is selected. The slower crystallization rate can restrain the movement of PC molecular chains, so that the stress of PC is slowly released, and the equilibrium state is better reached, giving the material better creep resistance and stress cracking resistance.

[0027] (4) The crack modifier of the present invention can give the material higher ductility and toughness, promote the compatibility of several phases of the material, avoid material delamination due to poor compatibility, and give the surface of the product a comfortable touch. DETAILED DESCRIPTION

[0028] The present invention is further illustrated by the following examples, but any example or combination thereof should not be construed as limiting the scope or implementation of the present invention. Without departing from the spirit and scope of the present invention, those skilled in the art may make any modifications or changes to the technical solution of the present invention, and such modifications and changes are also included in the scope of the present invention.

[0029] In the examples, if the specific conditions are not specified, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for all reagents or instruments, they are all conventional products that can be purchased commercially. In order to better illustrate the present invention, numerous specific details are provided in the specific embodiments below. It should be understood by those skilled in the art that the present invention can be implemented equally without certain specific details. In other embodiments, methods, means, equipment and steps well known to those skilled in the art are not described in detail to highlight the gist of the present invention.

[0030] Examples 1 to 8

[0031] Examples 1 to 8 provide a crack-resistant high-performance halogen-free flame-retardant PC alloy material and a preparation method thereof, the method specifically comprising the following steps:

[0032] According to the weight proportions of the formula components in Table 1, the toughening agent, crack modifier and chemical resistance modifier are weighed separately and then blended to ensure uniform dispersion, and then added into a high-speed mixer with the remaining components according to the above weight proportions, fully mixed at a rate of 100 rpm / min, and then fed into a twin-screw extruder for blending and granulation. If the flame retardant is a liquid, it is fed separately from a liquid pump in a corresponding proportion; the extrusion process is selected to carry out melt extrusion under the conditions of an extrusion temperature of 240-270°C and a screw speed of 200-500 rpm, and cooled for granulation to obtain the corresponding product.

[0033] Among them, the materials in Table 1 are as follows:

[0034] PC-1: PC from Cangzhou Dahua, molecular weight 27000;

[0035] PC-2: PC from Cangzhou Dahua, molecular weight 23000;

[0036] BDP: Wansheng Chemical;

[0037] ABS: Bulk ABS with 14% rubber content produced by petrochemical plants;

[0038] MBS: Zhong Yuan;

[0039] SEBS-g-MAH: Jiayirong, MAH content 1.8wt.%;

[0040] POE-g-MAH: Jiayirong, MAH content 1.6wt.%;

[0041] PS-g-MAH: Jiayirong, MAH content 1.5wt.%;

[0042] ABS-g-MAH: Jiayirong, MAH content 1.5wt.%;

[0043] PET: Yizheng Chemical Fiber, viscosity 0.65;

[0044] Talc: Talc, Liaoning Xinda, particle size 5000 mesh.

[0045] Lubricant: PETS, commercially available

[0046] Antioxidant: 1076, 168, BASF, the compound ratio is 1076:168=1:1.

[0047] Anti-drip agent: 50% SAN + 50% PTFE coated anti-drip agent, commercially available.

[0048] The performance testing and evaluation methods for materials are as follows:

[0049] ①Tensile yield strength, Izod notched impact strength and flame retardancy tests are carried out in accordance with ISO527, ISO180 and UL94 standards respectively.

[0050] ② Creep deformation: The specimen is a standard dumbbell-shaped specimen of plastic, with a thickness of 4mm, a width of 10mm, and a gauge length of 50mm. The test rate is set to 10mm / min, that is, the tensile speed of the specimen is 10mm per minute. Start the tensile test and gradually apply tension to 45MPa at a rate of 10mm / min. Keep the tension stable for 2 hours without applying other external forces. Observe the spline deformation after 2 small tests.

[0051] ③ Cracking of screw columns: Select PA3.5*10 self-tapping screws, select a torque of 0.8N·m, and tap into screw columns with an inner diameter of 2.8cm and an outer diameter of 4.0cm. Tap into 30 screw columns in total. After leaving them for 2 months, remove the screws and observe for cracking.

[0052] ④ Soak in anti-rust oil: Same as tapping conditions ③. After tapping, leave it for 1 day to get balanced, then soak the screw column in anti-rust oil for 5 minutes. Take it out, rinse it and leave it for 2 months before observing the cracking ratio.

[0053] ⑤Surface touch: Material injection-molded rough leather pattern sample, touch with index finger to evaluate the comfort of material touch:

[0054] ○—comfortable; △—medium; ×—average;

[0055] Table 1 Example formula weight parts

[0056]

[0057] Comparison between Examples 1 and 2 and Comparative Examples 1, 4 and 5 shows that the addition of grafts of SEBS or POE and maleic anhydride can effectively improve the notched impact strength, ductility and creep resistance of the material, and greatly improve the cracking behavior and surface touch of the material; while the use of PS-g-MAH materials (Comparative Example 4) will cause insufficient impact of the material, poor ductility and cracking. The effects of ABS-g-MAH and PS-g-MAH are not much different; it can be seen that to change the cracking behavior of the material system of the present invention, it is necessary to improve it with grafts of some elastomers such as SEBS or POE and maleic anhydride. Comparison between Example 3 and Comparative Example 2 shows that the addition of talcum powder can improve the notched impact strength and creep resistance of the material, significantly improve the flame retardant failure problem of pure phosphate flame retardants after thermal aging, and improve the cracking behavior of the material. From the comparison of Examples 4-8 with Comparative Examples 3 and 6, it can be seen that adding chemical resistance modifiers to the halogen-free flame retardant PC alloy material system can improve the flame retardant failure problem after thermal aging, significantly improve creep resistance and improve the cracking behavior of the material, especially the cracking behavior of the material immersed in rust-proof oil. However, the amount added should not be too much. If too much is added, the material will degrade and become brittle, and the elastomer graft will be difficult to compensate for the attenuation.

[0058] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A crack-resistant halogen-free flame-retardant PC alloy material, characterized in that: The composition comprises the following components in parts by weight: The crack modifier is one or more of SEBS grafted maleic anhydride and POE grafted maleic anhydride.

2. The crack-resistant halogen-free flame-retardant PC alloy material according to claim 1, characterized in that: The PC resin is a PC having a weight average molecular weight of 21000-33000 or a compound of several PCs.

3. The crack-resistant halogen-free flame-retardant PC alloy material according to claim 1, characterized in that: The halogen-free flame retardant is one or more of bisphenol A-bis(diphenyl phosphate), triphenyl phosphate, resorcinol bis(diphenyl phosphate), solid phosphate, and phosphazene.

4. The crack-resistant halogen-free flame-retardant PC alloy material according to claim 1, characterized in that: The toughening agent is one or more of methyl acrylate-butadiene-styrene, styrene-butadiene-acrylonitrile and ethylene-methyl acrylate.

5. The crack-resistant halogen-free flame-retardant PC alloy material according to claim 1, characterized in that: The chemical resistance modifier is a crystalline resin selected from ethylene terephthalate with a viscosity of 0.65-0.

85.

6. The crack-resistant halogen-free flame-retardant PC alloy material according to claim 1, characterized in that: The talc powder is talc powder with a particle size of 3000-5000 meshes and a surface that has not been treated with a coupling agent.

7. The crack-resistant halogen-free flame-retardant PC alloy material according to claim 1, characterized in that: The lubricant is one or more of ethylene bisstearamide, polyethylene wax, polypropylene wax, ethylene-vinyl acetate copolymer, and pentaerythritol tetrastearate.

8. The crack-resistant halogen-free flame-retardant PC alloy material according to claim 1, characterized in that: The antioxidant is one or both of antioxidant 1076 and antioxidant 168.

9. A method for preparing a crack-resistant halogen-free flame-retardant PC alloy material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: The toughening agent, crack modifier and chemical resistance modifier are first blended, then mixed with the remaining components at high speed, and then fed into a twin-screw extruder for blending and granulation; if the halogen-free flame retardant is liquid, it is fed separately from a liquid pump in a corresponding proportion.

10. The method for preparing the crack-resistant halogen-free flame-retardant PC alloy material according to claim 9, characterized in that: The extrusion process is to carry out melt extrusion at an extrusion temperature of 240-270° C. and a screw speed of 200-500 rpm, followed by cooling and granulation.